The Bioelectricity of Tofu Whey in Microbial Fuel Cell System with Lactobacillus bulgaricus - Inayati, Nor Sri; Aminin, Agustina L. N.; Suyati, Linda (JURNAL SAINS DAN MATEMATIKA, 2015)
Tofu whey is a byproduct of the manufacturing process tofu which containing the remains of protein, fat, carbohydrates and water-soluble substances that do not agglomerate. This study aim was to assess the potential of tofu whey as a substrate in the MFC system and to evaluate the effect of agitation speed to the potential difference generated in the MFC system using Lactobacillus bulgaricus. The potential difference in the variation of the substrate was measured against tofu whey, glucose and lactose. The potential difference with agitation speed variation was carried out at speed of 30, 60, 90, 125 and 250 rpm. The highest potential differences in the substrate variation showed relatively similar results, however they were achieved in different times, which the speed was dependent on the complexity of the substrate molecular structure. While the agitation of 90 rpm gave the highest potential difference. These results indicates that tofu whey potential to be used as a MFC substrate.